On the Inseparable Connection between Translation and Style - GJurchevska Atanasovska, Katarina (St. Kliment Ohridski University, Faculty of Education, 2018)
This paper deals with the complex and multifaceted nature of the relationship between translation and style. Bearing in mind the fact that this topic has not been very much systematically researched sо far, this paper aims at emphasising the mutual relationship between these two notions from different perspectives and through various theoretical insights. Despite being an important feature of the original, style also affects the translated work itself and can be perceived as a reflection of translator’s language and stylistic preferences. These considerations encourage comparative research with regards to translation practice. Furthermore, they tackle the cognitive dimension of the relationship between translation and style, which accentuates the role of the reader (who might also be a translator) within the overall creative process.
Keywords: style, translation, original, mind-style, reader, stylistic effect